(untitled) (Journal of Economics and Sustainability, 2023)
African countries’ endorsement of the African Continental Free Trade Area (AfCFTA) agreement framework has been regarded as a potential game-changer for intra-African trade and key to unlocking sustained economic growth and development. The euphoria surrounding this proposed introduction of a single continental market for goods and services, with free movement of businesses, persons, and investments, is closely linked to the positive relationship between trade and development as documented in the literature. However, it needs to be clarified from the literature what role overlapping trade flows may play in limiting the potential of the AfCFTA to boost intra-trade in Africa. This paper constructs trade overlap and trade expansion indices between Nigeria and selected African countries to investigate the scope for expansion of agricultural trade between Nigeria and the selected trading partners. The study finds the existence of considerable trade overlap and export expansion potential for Cassava among other agricultural products, between Nigeria and Equatorial Guinea, Guinea Bissau, Mauritania, and Sierra Leone. The study then opines that any overlapping trade flows that currently exist in the trade of Cassava between the selected partners can be redirected following the expected removal of customs tariffs once the AfCFTA is fully implemented.